CRISPR-HOLMES-based NAD+ detection - Zhuang, Songkuan; Hu, Tianshuai; Zhou, Hongzhong; He, Shiping; Li, Jie; Zhang, Yuehui; Gu, Dayong; Xu, Yong; Chen, Yijian; Wang, Jin (Frontiers in Bioengineering and Biotechnology, 2024)
Studies have indicated that intracellular nicotinamide adenine dinucleotide (NAD + ) level is associated with the occurrence and development of many diseases. While traditional NAD + detection techniques are time-consuming and may require large and expensive instruments. We recently found that the CRISPR-Cas12a protein can be inactivated by AcrVA5-mediated acetylation and reactivated by CobB, using NAD + as the co-factor. Therefore, here in this study, we created a CRISPR-Cas12abased one-step HOLMES(NAD + ) system for rapid and convenient NAD + detection with the employment of both acetylated Cas12a and CobB. In HOLMES(NAD + ), acetylated Cas12a losses its trans-cleavage activates and can be reactivated by CobB at the presence of NAD + , cutting ssDNA reporters to generate fluorescence signals. HOLMES(NAD + ) shows both sensitivity and specificity in NAD + detection and can be used for quantitative determination of intracellular NAD + concentrations. Therefore, HOLMES(NAD + ) not only provides a convenient and rapid approach for target NAD + quantitation but also expands the application scenarios of HOLMES to non-nucleic acid detection.